ANALISIS PENDAPATAN DAN KOMPOSISI AGROFORESTRY PETANI DI DESA BANGKA PAU, KECAMATAN POCO RANAKA, KABUPATEN MANGGARAI TIMUR - Marsela Cerlina; Paulus Un; Nixon Rammang (Wana Lestari, 2021)
This study aims to analyze farmers income and Agroforestry composition. This research was conducted in the village of Bangka Pau, Poco Ranaka District, East Manggarai Regency which was carried out for 3 months, from June - August 2020. This study used a survey method with data analysis using descriptive and quantitative analysis. The data is processed using the formula for calculating farmers' income, namely: Production x Price, while the income is: the difference between Revenue - Costs, dan Costs = Fixed costs + Variable costs, Total costs (TC) = TFC + TVC (Fixed Variable Costs). The results showed that the Agroforestry component in the research location had a mixed garden cropping pattern. Such as coffee (Coffea canephora sp), cloves (Syzygium aromaticum), banana (Musa paradisiaca), taro sweet potato (Ipomoea batatas) and rice fields, for forestry crops such as: Sengon (Paraserianthes falcatarian), Ampupu (Eucalyptus urophylla), Sureng (Colocasia esculenta), Jack fruit (Artocarpus heterophyllus). Most of the people in Bangka Pau Village work as subsistence workers, because the community wants to choose agricultural land because the soil fertility level is very good and can grow agricultural and forestry crops. And the status of the land they are working on is their own land. The level of education also affects the knowledge and ability of farmers in managing their farming business optimally. Farmers in Bangka Pau Village earn income from plantation products or from farmers' Agroforestry systems. For own forestry plants per tree is Rp. 1.000.000 – 2. 000000 it also depends on the size of the tree. The total cost incurred by farmers from the Agroforestry component in Bangka Pau Village per year is Rp. 42.,450.000 with an average farmer of Rp. 71.575.000. Total income received by farmers from the Agroforestry component in Bangka Pau Village annually which is received by farmers in one year is Rp. 8.722.085.000 with an average per farmer of Rp. 145.680.833 per year.